Grammar Consciousness-Raising Activities and Iranian EFL Learners' Attitudes toward English Language - Farrokhlagha Heidari; Nurullah Mansourzadeh (Journal of Education and Learning (EduLearn), 2014)
The first purpose of this study was to investigate the effect of consciousness-raising (C-R) activities on learning grammatical structures by Iranian EFL learners. The second one was to investigate the effect of gender through C-R activities and tasks. Finally, this study wanted to investigate the Iranian students’ attitudes toward learning English prior to and after applying the C-R activities. An attitude questionnaire was use to investigate the participants' attitudes toward learning English before and after applying C-R activities. Data analysis indicated that using C-R activities in is significantly more effective than the traditional approaches. Regarding gender, male outperformed females. Therefore, it is recommended that other teachers consider C-R activities as useful options in teaching other aspects of language. Based on the statistics and findings, Iranian students’ attitudes toward learning English language were not much different prior to and after applying C-R activities.